Analisis Probabilitas Kebangkrutan Bank Umum Swasta Nasional di Masa Pandemi - Puri, Pustika Ayuning; Pamungkas, Giantoro; Nurhasanah, Siti; Farikhi, Alfan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
At the end of 2019, the world was shocked by the phenomenon of the Covid-19 virus which caused significant changes to the economies of all countries, including Indonesia, where to date 6 million cases have been recorded. The implementation of the Large-Scale Social Restrictions (PSBB) policy implemented by the government has had an impact on the country's economic sector where many companies have closed down. This bankruptcy occurs due to financial distress, which is a condition where a company or individual cannot generate sufficient income or profit. Based on this phenomenon, researchers are interested in conducting research regarding the bankruptcy probability analysis of national private commercial banks listed on the Indonesian Stock Exchange. This research uses quantitative methods with secondary data obtained from company financial reports for 3 years, namely from before the 2019 to 2021 pandemic which will be processed using the Altman Z-Score and Zmijewski X-Score analysis methods.